2013 IEEE International Conference on Industrial Technology (ICIT) 2013
DOI: 10.1109/icit.2013.6505833
|View full text |Cite
|
Sign up to set email alerts
|

Improving feature-based object recognition for X-ray baggage security screening using primed visualwords

Abstract: We present a novel Bag-of-Words (BoW) representation scheme for image classification tasks, where the separation of features distinctive of different classes is enforced via class-specific featureclustering. We investigate the implementation of this approach for the detection of firearms in baggage security X-ray imagery. We implement our novel BoW model using the Speeded-Up Robust Features (SURF) detector and descriptor within a Support Vector Machine (SVM) classifier framework. Experimentation on a large, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
74
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(83 citation statements)
references
References 20 publications
2
74
0
Order By: Relevance
“…In the classification of baggage containing handguns they reported that the method does not work well in isolation but results can be improved using the extra information available from the colour image (indicating material type). In an extension of [29], Turcsany et al [30] present a BoW model using the Speeded-Up Robust Features (SURF) [31] and a Support Vector Machine (SVM) [32] classifier for automated object recognition within 2D X-ray baggage imagery. Correct classification rates in excess of 99% and a false positive rate of approximately 4% are demonstrated on a diverse dataset.…”
Section: Introductionmentioning
confidence: 99%
“…In the classification of baggage containing handguns they reported that the method does not work well in isolation but results can be improved using the extra information available from the colour image (indicating material type). In an extension of [29], Turcsany et al [30] present a BoW model using the Speeded-Up Robust Features (SURF) [31] and a Support Vector Machine (SVM) [32] classifier for automated object recognition within 2D X-ray baggage imagery. Correct classification rates in excess of 99% and a false positive rate of approximately 4% are demonstrated on a diverse dataset.…”
Section: Introductionmentioning
confidence: 99%
“…This poses an interesting challenge for the use of automatic object recognition approaches akin to the prior work of [1,2,3,4]. In addition, an associated ability to automatically assess the underlying complexity of a given X-ray baggage image facilitates the potential of "auto-clearing" low complexity baggage items (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Baştan et al [1] considers the concept of Bag-of-Visual-Words (BoVW) within X-ray baggage imagery using Support Vector Machine (SVM) classification with SIFT feature descriptors [7] achieving performance of 0.7, 0.29, 0.57 recall, precision and average precision, respectively. Turcsany et al [4] followed a similar approach, extending the work of [1], using BoVW with SURF feature descriptors [8] and SVM classification together with a modified version of vocabulary generation to yield 99.07% true positive, and 4.31% false positive on firearms detection over 2000 examples. A BoVW approach with SIFT feature descriptors, augmented with SPIN X-ray intensity features [9], and SVM classification is also used in [3] for the classification of single and dual view X-ray images with best average precisions achieved for gun and laptop objects of 94.6% and 98.2%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations